Evaluation of the National cervical cancer surveillance program in Bangladesh: Performance, strengths, and opportunities for improvement. - Md Foyjul Islam; Ashrafun Nessa; Quazi Ahmed Zaki; Shah Ali Akbar Ashrafi; Md Omar Qayum; Mohammad Rashedul Hassan; Tahmina Shirin (PLOS Global Public Health)
Cervical cancer (CC) is the second most prevalent cancer among women in Bangladesh, with 9,640 new cases and 5,826 deaths annually. Since 2018, the Electronic Data Tracking with Population-Based Cervical and Breast Cancer Screening Program (EPCBCSP) has been implemented nationwide across 601 health centers, utilizing Visual Inspection with Acetic Acid (VIA) for CC screening. However, the system had not been evaluated until now. This study aims to assess the performance of EPCBCSP and identify its strengths and challenges. We evaluated EPCBCSP using the updated guidelines from the Centers for Disease Control and Prevention(CDC) in 2023. Data were collected from central level stakeholders and from stakeholders at one colposcopy and one VIA center in each of four selected divisions of Bangladesh. Interviews with 42 stakeholders assessed simplicity, flexibility, acceptability, stability and usefulness attributes. Data quality was assessed by surveillance data review. Percentage scores were calculated and ranked as follows: excellent (≥ 90%), Very good (≥ 80%- < 90%.), good (≥60%- < 80%), average (≥50%- < 60%) and poor (≤50%).The overall system performance was rated as good (score:77.20%). The system's simplicity (score: 91.61%) and usefulness (score:91.61%) were ranked as "excellent". The acceptability (score: 85.29%) was ranked as "very good and flexibility (score:71.90%) was rated as "good". Stability (percentage score: 53.25%) was considered average. Furthermore, data quality was assessed as average based on missing values (13.11%.) Electronic data tracking system, instant test report availability and "see and treat" policies were identified as strengths by stakeholders, while dedicated staff shortages and motivating participants were main challenges. The evaluation EPCBCSP in Bangladesh indicates overall good performance, excelling in simplicity and usefulness. However, improvements are needed in stability and data quality. Strengthening surveillance efforts addressing shortages of dedicated staff and participant motivation will further enhance the effectiveness of the program, crucial for reducing CC burden.